Coffee consumption protects against progression in liver cirrhosis and increases long-term survival after liver transplantation - Friedrich, Kilian; Wannhoff, Andreas; Rupp, Christian; Antoni, Christoph Helmer; Stremmel, Wolfgang; Weiss, Karl Heinz; Schemmer, Peter; Gotthardt, Daniel (Journal of gastroenterology and hepatology, 2016)
Background Therapeutic options to treat progression of end-stage liver disease (ESLD) or improve long-term survival after liver transplantation remain scarce. We investigated the impact of coffee consumption under these conditions. Methods We recorded coffee consumption habits of 379 patients with ESLD awaiting liver transplantation and 260 patients after liver transplantation. Survival was analyzed based on coffee intake. Results One hundred ninety-five patients with ESLD consumed coffee on a daily basis, while 184 patients did not. Actuarial survival was impaired (P = 0.041) in non-coffee drinkers (40.4 ± 4.3 months, 95% confidence interval [CI]: 32.0-48.9) compared with coffee drinkers (54.9 ± 5.5 months, 95% CI: 44.0-65.7). In subgroup analysis, the survival of patients with alcoholic liver disease (ALD; P = 0.020) and primary sclerosing cholangitis (PSC; P = 0.017) was increased with coffee intake while unaffected in patients with chronic viral hepatitis (P = 0.517) or other liver disease entities (P = 0.652). Multivariate analysis showed that coffee consumption of PSC and ALD patients retained as an independent risk factor (odds ratio [OR]: 1.94; 95% CI: 1.15-3.28; P = 0.013) along with MELD score (OR: 1.13; 95% CI: 1.09-1.17; P = 0.000). Following liver transplantation, long-term survival was longer in coffee drinkers (coffee: 61.8 ± 2.0 months, 95% CI: 57.9-65.8) than non-drinkers (52.3 ± 3.5 months, 95% CI: 45.4-59.3; P = 0.001). Conclusions Coffee consumption delayed disease progression in ALD and PSC patients with ESLD and increased long-term survival after liver transplantation. We conclude that regular coffee intake might be recommended for these patients.
First published: 15 February 2016
Gesehen am 05.10.2018